Two-step synthesis of reduced graphene oxide with columnar-shaped ZnO composites and their photocatalytic performance with natural dye - Yadav R.; Kumar V.; Saxena V.; Singh P.; Singh V.K. (My University, 2025)
Composites of ZnO with reduced graphene oxide were prepared in two-step synthesis process with constant temperature in variation with pH values. The synthesized composites were characterized and the results suggest that ZnO structure in the composites has a columnar morphology with an average diameter ranging 0.8–1.57 μm. The obtained properties of the composites with the present method confirmed that the material morphology influences the absorption and photocatalytic activity of natural dye under sunlight irradiation. The result shows that the maximum degradation efficiency is 64.40% achieved in 120 min. © 2019, Australian Ceramic Society.